Answer:
total is 47.70
Step-by-step explanation:
change is $12.30
Step-by-step explanation:
![{sin}^{2} A + {cos}^{2} A = 1 \\ lhs = {sin}^{2} A + {cos}^{2} A \\ = {sin}^{2} A + 1 - {sin}^{2} A \\ = 1 \\ = rhs \\ \therefore \: {sin}^{2} A + {cos}^{2} A = 1 \\](https://tex.z-dn.net/?f=%20%7Bsin%7D%5E%7B2%7D%20A%20%2B%20%20%7Bcos%7D%5E%7B2%7D%20A%20%20%3D%201%20%5C%5C%20lhs%20%3D%20%20%7Bsin%7D%5E%7B2%7D%20A%20%2B%20%20%7Bcos%7D%5E%7B2%7D%20A%20%20%5C%5C%20%20%3D%20%20%7Bsin%7D%5E%7B2%7D%20A%20%2B%20%201%20-%20%7Bsin%7D%5E%7B2%7D%20A%20%20%5C%5C%20%20%3D%201%20%5C%5C%20%20%3D%20rhs%20%5C%5C%20%20%5Ctherefore%20%5C%3A%20%20%7Bsin%7D%5E%7B2%7D%20A%20%2B%20%20%7Bcos%7D%5E%7B2%7D%20A%20%20%3D%201%20%5C%5C%20)
Answer:
54
Step-by-step explanation:
Answer:
6 i think
Step-by-step explanation:
Answer:
z = -4 1/2
Step-by-step explanation:
1. First change the mixed fractions to improper fractions so it's easier
![\frac{16}{5\\}/(z-\frac{1}{2}) = \frac{8}{3}/(z+\frac{1}{3})](https://tex.z-dn.net/?f=%5Cfrac%7B16%7D%7B5%5C%5C%7D%2F%28z-%5Cfrac%7B1%7D%7B2%7D%29%20%3D%20%5Cfrac%7B8%7D%7B3%7D%2F%28z%2B%5Cfrac%7B1%7D%7B3%7D%29)
2. Simplify
![\frac{32}{5(2z-1)} = \frac{8}{3z+1}](https://tex.z-dn.net/?f=%5Cfrac%7B32%7D%7B5%282z-1%29%7D%20%3D%20%5Cfrac%7B8%7D%7B3z%2B1%7D)
3. Cross multiply
![32(3z+1) = 5(2z-1) * 8](https://tex.z-dn.net/?f=32%283z%2B1%29%20%3D%205%282z-1%29%20%2A%208)
4. Simplify again (distributive property)
![32(3z+1) = 40(2z-1)](https://tex.z-dn.net/?f=32%283z%2B1%29%20%3D%2040%282z-1%29)
5. Distributive property
![40(2z-1) -> 80z-40](https://tex.z-dn.net/?f=40%282z-1%29%20-%3E%2080z-40)
![96z+32=80z-40](https://tex.z-dn.net/?f=96z%2B32%3D80z-40)
6. Subtract 32 from both sides
![96z+32-32 = 80z-40-32](https://tex.z-dn.net/?f=96z%2B32-32%20%3D%2080z-40-32)
7. Simplify
![96z = 80z-72](https://tex.z-dn.net/?f=96z%20%3D%2080z-72)
8. Subtract 80 from both sides
![96z-80z=80z-72-80z](https://tex.z-dn.net/?f=96z-80z%3D80z-72-80z)
9. Simplify
![16z=-72](https://tex.z-dn.net/?f=16z%3D-72)
10. Divide both sides by 16
![\frac{16z}{16}=\frac{-72}{16}](https://tex.z-dn.net/?f=%5Cfrac%7B16z%7D%7B16%7D%3D%5Cfrac%7B-72%7D%7B16%7D)
11. Simplify
![z=-\frac{9}{2} -> also = -4\frac{1}{2}](https://tex.z-dn.net/?f=z%3D-%5Cfrac%7B9%7D%7B2%7D%20-%3E%20also%20%3D%20-4%5Cfrac%7B1%7D%7B2%7D)
Sorry if it was too long but hope this helps! :)
And also try using symbolab cuz it gives step by step explanations it's really good!